Exploring Flow Experience in Mountain Climbers: Insights for Enhancing Educational Leadership - Anis Nurul Farida; Onny Fransinata Anggara (Al-Qalam Institue, 2026)
Flow experience in mountain climbing can be understood as an individual’s state of complete absorption when facing challenges that match their abilities. This study aims to explore the meaning of flow experience in mountain climbers from a phenomenological perspective and examine its implications for educational leadership. A qualitative phenomenological approach was employed, using in-depth interviews and member checking to ensure the validity of the data. The interview results were analyzed through Interpretative Phenomenological Analysis (IPA). The findings revealed five key themes of flow experience among mountain climbers: (1) engaging in meaningful experiences by enjoying nature and fostering personal and social connections, (2) achieving a state of immersion characterized by focus, safety, and self-control, (3) relying on preparation, skills, and decision-making to face climbing challenges and risks, (4) using mountain climbing as a process for self-development, reflection, and value formation, and (5) experiencing positive emotional, physical, and psychological effects. These insights suggest that the principles of flow, such as focus, intrinsic motivation, and adaptive decision-making, can be applied to educational leadership to enhance teacher engagement, decision-making under pressure, and personal development.